Conductometric determination of formation constants of tris(2-pyridyl)methylamine and titanium (III) in water-acetonitryl mixture. - Rezayi, Majid; Kassim, Anuar; Ahmadzadeh, Saeid; Yusof, Nor Azah; Naji, Abolfazl; Ahangar, Hossein Abbastabar (Electrochemical Science Group, 2011)
A conductance study of the interaction between titanium (III) cation and tris(2-pyridyl) methylamine (tpm), in water-acetonitrile mixtures was carried out at various temperatures. The formation constants of the resulting 1:1 complexes were determined from the molar conductance-mole ratio data. The stability constants of 1:1 (M:L) complexes of tpm with titanium (III) cation, the Gibbs standard free energies (ΔGc oscript), the standard enthalpy changes (ΔHc oscript) and the standard entropy changes (ΔSc oscript) for the formation of these complexes in acetonitrile-water (AN-H2O) binary mixtures have been determined conductometrically. The stability constants of the complexes were obtained from fitting of molar conductivity curves using a computer program, GENPLOT.